Efeitos do ranelato de estrôncio sobre o tempo de osseointegração de implantes dentários de titânio instalados em tíbia e em fêmur de coelhos” - Magalhães, Glívia Maria Silveira (2009)
The integration of titanium dental implants in bone has been reported extensively over the last few decades beginning with the original work of Branemark and co-workers. The use of titanium endosseous dental implants in the treatment of edentulous or partially edentulous patients has become an alternative to restore function and esthetics, however, this results depend on the quantity and quality of the maxillary or mandibular bone. Osteoporosis is a disease that influences the quality of bone tissue such that it may become susceptible to fracture. Significant relationship have been reported between oral bone and skeletal bone mass in postmenopausal women. Osteoporosis could, therefore be considered a risk factor for osseointegration of dental implants, but this is still controversial. Strontium ranelate is a new therapy for the treatment and prevention of osteoporosis that may dissociate bone formation and bone resorption by allowing continued production of bone while decreasing bone resorption. The purpose of this study was to determine the effect of systemic strontium ranelate therapy on early dental implant osseointegration based on torque-removal values in rabbits. Sixty-four identical titanium dental implants were placed using a standardized surgical protocol in the bilateral distal femur and proximal tibia of 16 New Zealand white rabbits (64 implants total). One week before implant placement, 8 rabbits were given doses of strontium ranelate (625mg/kg/day) until euthanized. The other 8 rabbits were untreated controls. One rabbit of each group were sacrificed in time of 15, 30, 45, 60, 75, 90, 105, 120 days, and torque-removal values were determined using a digital torque wrench for all implants. Analyses of torque data showed no statistical differences between the strontium ranelate and control groups. Based on the findings of this study, we can conclude that the time of 15 to 120 days of strontium ranelate administration does not interfere with the timing of early dental implant osseointegration in an animal model.